"Die zerschossene Fassade des Vorwärts-Gebäudes in der Lindenstrasse in Berlin". Aus: Album XI - Haeckel, Otto,
"Die zerschossene Fassade des Vorwärts-Gebäudes in der Lindenstrasse in Berlin". Aus: Album XI.